Decision on the selection of the best height-diameter ratio for the optimal design of 13, 000 m3 oil storage tank. Issue 1 (1st January 2020) - Agboola, O. O.; Akinnuli, B. O.; Kareem, B.; Akintunde, M. A.
Abstract: The decision on the selection of the best height-diameter ratio for the optimal design of oil storage tanks is a difficult task because there are so many criteria to be considered in selecting the most appropriate alternative. In this study, Multi-Criteria Decision Analysis (MCDA) was used by adopting Criteria Importance Through Inter-criteria Correlation (CRITIC) in determining the objective weight of the criteria. The six criteria considered in this study are: Area occupied by the tank (m 2 ), Weight (kg), Wind Moment (Nm), Seismic Ringwall Moment RWM (Nm), Base shear (N) and Estimated Cost (₦) and the objective weights assigned to them by CRITIC are 0.2356, 0.2607, 0.1238, 0.1249, 0.1196 and 0.1354, respectively. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) was then used to rank each of the alternatives based on the objective weight obtained through CRITIC. The objective of obtaining an optimal design of a 13, 000 m 3 storage tank that will occupy less space, weighty to resist wind load and seismic overturning at a moderate (low) cost was achieved by Alternatives A4 and A5 (height-diameter ratios of 0.8 and 0.9). To validate the ranking result obtained by the TOPSIS method, another MCDA method, VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) was employed to compare the results. Validation of the TOPSIS method by VIKOR method revealed that there was high consistency in the results obtained, with a very high Spearman's rank correlation coefficient of 0.8727. Sensitivity analysis was also done to ascertain the robustness of the results.